Development and validation of donor adverse reaction severity grading tool: enhancing objective grade assignment to donor adverse events. Issue 6 (25th May 2020) - Townsend, Mary; Kamel, Hany; Van Buren, Nancy; Wiersum‐Osselton, Johanna; Rosa‐Bray, Marilyn; Gottschall, Jerome; Rajbhandary, Srijana
Abstract : BACKGROUND: Uniform and consistent reporting and comparison of donor adverse events (DAEs) and severity are well‐recognized challenges for donor hemovigilance (DHV). While the 2014 Standard for Surveillance of Complications Related to Blood Donation (SSCRBD), developed by hemovigilance experts from AABB, the International Society of Blood Transfusion, and International Hemovigilance Network, established the DAE definitions, no specific guidelines were provided to grade severity. A group of subject matter experts developed the Severity Grading Tool for Blood Donor Adverse Events (SGT) to enhance objective assignment of severity and conducted a study to validate the tool. STUDY DESIGN AND METHODS: Between January 8, 2019, and February 28, 2019, participants graded severity of 32 cases (34 DAEs) using the SGT. Comments boxes allowed participants to provide rationale for selecting a severity grade for each case. Agreement with expert grading among study participants was evaluated using percentage agreement. Inter‐rater reliability was evaluated by Kendallʼs coefficient of concordance (W). The final SGT was revised based on validation study results and feedback received. RESULTS: The overall agreement was almost perfect with W = 0.84 (confidence interval [CI], 0.78‐0.90). Of 34 DAEs, respondent agreement with expert grading of more than 90% was reached for 18 DAEs, 80% to 90% for six DAEs, 70% to 80% for six DAEs, and less than 70% for four DAEs. CONCLUSION: The development and validation of a uniform SGT with objective criteria for assigning severity of DAEs used together with standard reaction definitions will provide opportunities for comparison between blood centers and systems to enhance the field of DHV. Abstract : See editorial on page 1115–1117,  in this issue